Capturing Finger and Palm Impressions Using a Hand Cream and Thermochromatic Paper1. Issue 5 (18th July 2013) - Bond, John W.
Abstract: An inkless set of finger and palm impressions has been obtained on thermochromatic paper by incorporating the protic solvent butylene glycol into a base hand cream mixture, which is rubbed into the hands for 30 sec before donation. This requires no washing of the hands before or after donation, removing many of the difficulties associated with inked impressions. In a random trial of 50 male and 50 female participants (mean age 41 years), 96 found the hand cream pleasant and easy to use and all produced identifiable finger and palm impressions. Following donation, participants continued to rub the hand cream into their hands. Impressions were visible immediately after donation and have not exhibited fading 2 years after being taken. 10% of participants produced impressions that captured third‐level detail, the variation between participants being thought to be associated with the amount of pressure applied during donation.